Evaluasi Pengunjung Terhadap Kualitas Pantai Palippis Sebagai Ruang Publik Tepian Air Berbasis Placemaking - Firmansyah Firmansyah; Slamet Tri Sutomo; Mukti Ali (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2021)
Palippis Beach is an underwater coastal tourism object (snorkeling) and a rest area, but there is a conflict with managers who prioritize finance and a lack of visitors from year to year, which causes Pantai Palippis being not optimal as a waterfront public space. The aim of this research is to determine the quality of Palippis Beach as a waterfront public space and the recommendations of its development based on the placemaking approach. This research was conducted from November 2019 until February 2020 (4 months). This research used primary and secondary data which collected by field surveys, questionnaires, interviews, documentation and literature studies. The research location takes a part of the rest area which is located between Polewali Mandar and Majene Regencies. The analysis used in this research is Importance Performance Analysis (IPA) method, activity mapping analysis (behavior mapping), and infrastructure analysis. The results showed that the quality value of Palippis Beach using the IPA questionnaire method gets a value of 83.50% which declared as a high quality because it is between 76% -100%. The intensity of use from Palippis Beach scores 54.54% on weekdays and 53.2% on holidays which is considered high because it is in the range of 51% -75%. There are several tourist infrastructure that still need to be equipped, such as tourism services, security, and cleanliness so quality improvement recommendations are required based on the four quadrants resulting from the Cartesian diagram of the IPA method. These directives are recommendations for the development, maintenance, utilization and adjustment of tourist area infrastructure in accordance with applicable standards.